Code-name downfall : the secret plan to invade Japan and why Truman dropped the bomb - Allen, Thomas B., 1929-; Polmar, Norman (New York : Simon & Schuster, 1995)
What would have happened if atomic bombs had not been dropped on Japan in August 1945? Distinguished military writer historians Thomas B. Allen and Norman Polmar answer that provocative question in Code-Name Downfall, a vivid and dramatic narrative of America's war in the Pacific, which would lead inevitably to massive amphibious assaults against the Japanese home islands. Based on newly declassified documents, personal interviews, and a decade of meticulous research, their book traces the progress of the Pacific War and reveals the top-secret details of the plans and preparations, on both the American and Japanese sides, for an invasion that would be far more complex - and costly in human lives - than the D-Day landings in France.
Some historians have argued that the use of the atomic bomb was both unnecessary and immoral. Allen and Polmar totally refute that argument and back up their position with hard evidence. More than that, the authors describe the deep personal beliefs of the men who determined the course of the war, not only from the vantage point of history, but also in the context of that terrible time. In the end, with new knowledge and understanding of the events during these climactic days of the war, readers will be able to decide for themselves whether Truman's decision was justified.
Includes bibliographical references (p. [307]-340) and index.
Keywords: World War, 1939-1945 -- United States; World War, 1939-1945 -- Japan; Strategy; Atomic bomb